Prolonged Face Mask Use During COVID-19 Pandemic Contributes to Increased Symptoms and Signs of Dry Eye: A Systematic Literature Review - Anak Agung Fridami Dewi; I Gede Bayu Utama Putra (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Introduction: Face mask has been a vital protective equipment against COVID-19 in this pandemic era. Several ophthalmic complaints have been associated with face mask use, leading to the term